2017
DOI: 10.5812/numonthly.45866
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Alterations and Increased Cardiovascular Risk in Chronic Renal Failure

Abstract: Patients suffering from chronic renal failure have a higher burden of cardiovascular events, which increases in a dose-dependent fashion as renal function worsens. Increased cardiovascular risk in these patients is thought to be mediated by the simultaneous presence of both traditional and non-traditional cardiovascular risk factors, the latter being associated with renal impairment. Red blood cells are usually considered as carries of nutrients for tissues and respiratory gases, less so as compartments essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 81 publications
1
6
0
Order By: Relevance
“…To be noted that exposure of PS on uremic RBC membrane is expected to promote not only cell removal [59], but also procoagulant properties [60], and increased adhesion to endothelium decreasing NO release [61], an effect associated with CV mortality in ESRD. These findings may shed some light on the erythrocyte pathophysiology in ESRD, and further support the potential role of uremic RBCs per se as CV risk factor [37].…”
Section: Red Blood Cellsupporting
confidence: 64%
See 1 more Smart Citation
“…To be noted that exposure of PS on uremic RBC membrane is expected to promote not only cell removal [59], but also procoagulant properties [60], and increased adhesion to endothelium decreasing NO release [61], an effect associated with CV mortality in ESRD. These findings may shed some light on the erythrocyte pathophysiology in ESRD, and further support the potential role of uremic RBCs per se as CV risk factor [37].…”
Section: Red Blood Cellsupporting
confidence: 64%
“…The main cause of renal anemia is a reduced erythropoietin (EPO) production, though shortened RBC lifespan, uremic toxins, and inflammation also play a role [36]. Besides a reduction in their number, erythrocytes in the uremic milieu are also prone to many structural and functional impairments, including alterations in the production of nitric oxide, reduced antioxidant activity, increased adhesion to the endothelium and pro-coagulant activity, and modification in the composition of plasma membrane, all aspects that may jeopardize their properties [37].…”
Section: Red Blood Cellmentioning
confidence: 99%
“…Indeed, we and others have shown that RBCs form NO through nitrite reduction under hypoxia conditions and synthesize NO through an active endothelial nitric oxide synthase (eNOS) during normoxia, both contributing to the circulating NO pool [ 5 , 6 , 7 , 8 ]. These findings have raised the idea that alterations in such and other RBCs functions may lead to increased cardiovascular risk as already hypothesized in diabetes mellitus, coronary artery disease (CAD), hypertension and CKD [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as the uremic environment has been shown to impair several RBCs functions [ 13 ], studying the effects that the different therapies used in CKD could have on RBCs changes would add an important piece of knowledge to this intricate scenario.…”
Section: Introductionmentioning
confidence: 99%
“…Different mechanical obstacles that may exist in circulation cause visible deformation of the blood cells. Even blood plasma chemistry changes, caused by some liver or kidney diseases, lead to specific RBC membrane chemical changes that manifest themselves as deformations detectable by light microscopy [ 2 ]. Unfortunately, the light microscopy of native or even stained blood smears cannot detect chemical signatures carried by blood cells which are caused by other organ pathologies.…”
Section: Introductionmentioning
confidence: 99%